Biodiesel production from linseed oil and performance study of a diesel engine with diesel bio-diesel (Journal of Mechanical Engineering, 2009)
The use of biodiesel is rapidly expanding around the world, making it imperative to fully understand the impacts of biodiesel on the diesel engine combustion process and pollutant formation. Biodiesel is known as "the mono alkyl esters of long chain fatty acids derived from renewable lipid feedstock, such as vegetable oils or animal fats, for use in compression ignition (diesel) engines." Biodiesel was made by transesterification from linseed oil. In aspect of Bangladesh linseed can play an important role in the production of alternative diesel fuel. The climatic and soil condition of our country is convenient for the production of linseed (Linum Usitatissimum) crop. In the first phase of this work optimization of different parameters for biodiesel production were investigated. In the second phase the performance study of a diesel engine with diesel biodiesel blends were carried out. The results showed that with the variation of catalyst, methanol and reaction time; variation of biodiesel production was realized. About 88% biodiesel production was experienced with 20% methanol, 0.5% NaOH catalyst and at 550C. The results also showed that when compared with neat diesel fuel, biodiesel gives almost similar thermal efficiency, lower carbon monoxide (CO) and particulate matter (PM) while slightly higher nitrogen oxide (NOx) emission was experienced.Â  Keywords: Biodiesel, linseed oil, catalyst, alcohol and diesel emissions. doi:10.3329/jme.v39i1.1832 Journal of Mechanical Engineering, vol. ME39, No. 1, June 2008 40-44